Developing a Creative Entrepreneurship Education Model to Enhance Student’s Creativity and Innovation for Successful Completion of the Independent Entrepreneurship MBKM Program - I Gusti Putu Bagus Sasrawan Mananda; Ni Putu Eka Mahadewi (Jurnal Penelitian Pendidikan IPA, 2023)
In this study, the objective is to develop an innovative educational model for fostering creativity and innovation in aspiring entrepreneurs using the "learning by doing" approach, specifically through practical business experiences. The aim is to cultivate creativity and innovation among students, equipping them with the skills needed for entrepreneurial endeavors. By integrating students' creativity and innovation into entrepreneurship education, the research aims to instill an entrepreneurial mindset and contribute to reducing the high unemployment rate among educated individuals in Indonesia. This research was carried out at Udayana University's Faculty of Tourism, focusing on alumni who had completed entrepreneurship courses. The study employed a descriptive and verification research approach, with data presented as percentages and detailed descriptions. A purposive sampling technique was utilized, targeting undergraduate students who had taken entrepreneurship courses, resulting in a sample size of 100 individuals. Structural Equation Modeling (SEM) analysis using the Lisrel 8.0 software was the chosen analytical tool. The SEM analysis revealed that the t-values for both student creativity (6.80) and student innovation (6.56) exceeded the critical t-value of 1.85 at a 5% error rate. This led to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Ha).